Reconsideration of the Zincke salt: An efficient colorimetric chemosensor for detection of ethylamines - Kim, Jong H. (Spectrochimica Acta - Part A: Molecular and Biomolecular Spectroscopy, 2018)
In this work, an efficient colorimetric chemosensor for the detection of ethylamines using a pyridinium salt (the Zincke salt) is reported. Highly sensitive and selective reactivity of the Zincke salt enables colorimetric response of the Zincke salt solution to the ethylamines by showing well-defined visible color changes from colorless to the deep red. Furthermore, the Zincke salt thin film exhibits discernable color changes in response to ethylamine gas as well, which allows fabrication of simple, fast and portable strip- and textile-type ethylamine sensors.
Keywords: Chemosensor; Colorimetric chemosensor; Colorimetric sensors; Ethylamines; Pyridinium salts; Selective reactivity; Visible color changes; Zincke salts; Chemosensor; Colorimetric sensor; Ethylamines; The Zincke salt; Volatile organic compounds (VOCs)